(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The assessment of environmental traffic noise pollution in Uvwie local government area of Delta State, Nigeria was carried out using a well calibrated portable digital sound level meter (Model CEL-231). The sound level meter is an instrument used for measuring the exposure level of noise in the field. The measurement was done three times/day (Morning session 9am 10am, afternoon session 1pm 2pm and Evening session 4pm 5pm) and readings were taken. The mean results measured from the studied area ranged from 74.61dB (A) in the evening to 76.92dB (A) in the afternoon with mean average of 76.66dB (A).The obtained mean values of traffic noise when compared with the permissible level for road traffic noise of 65 decibels dB (A) in commercial area during the Day time, it was observed that the obtained mean level results exceeded the permissible standard limit. These high values can be attributed to poor maintenance of the vehicles, indiscriminate usage of pressure horns and present of heavy duty truck that load petroleum product and cargo containers from the Warri refinery and Warri port (Nigeria Port Authority) respectively. This study revealed that immediate health implication may not be observed at the present level, but long term health effects are probable in the nearest future.